BLACK STUDENTS MATTER: HOW TEACHERS EQUITABLY ENGAGE AFRICAN AMERICAN STUDENTS IN UNDERSTANDING CONCEPTUAL MATHEMATICS - Ahmad, Zarina A (East Carolina University, 2023)
In this participatory action research (PAR) study, I sought to understand how teachers implemented equitable and culturally responsive academic discourse to support African American students during mathematics instruction. Working with a group of teachers in a co-practitioner researcher (CPR) group, I examined to how teachers effectively planned and implemented culturally responsive academic discourse routines during mathematics instruction, engaged in plan-do-study-act cycles of inquiry, used protocols, and reflected on their pedagogical practices. In conducting evidence-based observations and post-observation conversations, teachers shifted their practices to be equitable and culturally responsive. Using qualitative methods to analyze data from documents, observation tools, coaching conversations, reflective memos, and artifacts from community learning exchange protocols (CLE), the findings are: (1) Teachers changed their academic discourse routines to foster equitable access; (2) observations and post-observation conversations facilitated by the school leader supported teachers to shift to culturally responsive practices. The research provides more insight for the teachers, the school, and the district on how to foster equitable engagement of African American students in conceptual mathematics and is useful to other leaders and teachers at site levels who want to engage in action research to understand and shift their instructional practices.
Keywords: Examine how teachers use equitable and culturally responsive academic discourse to engage African American students in learning mathematics; Mathematics--Study and teaching (Elementary); Culturally relevant pedagogy; African American students--Education (Elementary); Academic achievement; Educational equalization; Teacher-student relationships